2019
DOI: 10.21614/chirurgia.114.5.668
|View full text |Cite
|
Sign up to set email alerts
|

Monobloc Total Thyroidectomy Using Sealing Devices: Preliminary Results and Comparative Analysis

Abstract: Background: Dorinţa unei hemostaze perfecte a determinat industria echipamentelor medicale să producă instrumente "ideale" necesare unei tiroidectomii sigure. Astfel, instrumentele de hemostază-sigilare, cum ar fi LigaSure TM Small Jaw, Thunderbeat TM Open Fine Jaw şi Harmonic TM Focus au fost concepute pentru chirurgia tiroidiană. Scop: Scopul acestui studiu este de a prezenta rezultatele iniţiale ale utilizării acestor trei instrumente chirurgicale pentru efectuarea tiroidectomiei monobloc. Materiale and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…We noted that the use of the LigaSure TM Small Jaw device proved more efficient, in that it shortened the operative time, but the operative time was not statistically significantly different between the 2 groups. The utility of LigaSure TM Small Jaw in reducing operative time and controlling haemorrhage has been reported not only in surgery on the thyroid gland [8,9] but also in skin-sparing mastectomy for breast cancer [10]. This aspect has also been demonstrated in a meta-analysis that compared the LigaSure TM Small Jaw device to other methods of haemostasis/lymphostasis and found that the LigaSure TM Small Jaw shortened the operative time and reduced haemorrhage and other complications [11].…”
Section: Discussionmentioning
confidence: 88%
“…We noted that the use of the LigaSure TM Small Jaw device proved more efficient, in that it shortened the operative time, but the operative time was not statistically significantly different between the 2 groups. The utility of LigaSure TM Small Jaw in reducing operative time and controlling haemorrhage has been reported not only in surgery on the thyroid gland [8,9] but also in skin-sparing mastectomy for breast cancer [10]. This aspect has also been demonstrated in a meta-analysis that compared the LigaSure TM Small Jaw device to other methods of haemostasis/lymphostasis and found that the LigaSure TM Small Jaw shortened the operative time and reduced haemorrhage and other complications [11].…”
Section: Discussionmentioning
confidence: 88%